ANALYSIS OF 16528 INDIVIDUAL 24-HOUR AMBULATORY BLOOD PRESSURE MONITORING RECORDS REFERRED TO A HYPERTENSION UNIT FOR 23 YEARS - Azevedo, Isabel (2024)
Twenty-four hour ambulatory blood pressure (ABPM) is an essential tool in the evaluation of hypertensive patients. The present study consisted of the retrospective evaluation of 16528 ABPM records made at the Hypertension and Cardiovascular Risk Unit of ULS Matosinhos between January 2000 and December 2022 in patients with arterial hypertension, under medication and without previous cardiovascular events. This population (51% women, aged 18-80 years) was divided into 5 groups according to the total number of antihypertensive drugs prescribed, i.e. 1, 2, 3, 4 or >=5. About 29% of patients were on monotherapy. The in-office blood pressure (BP)-based hypertension control rate (<140/90 mm Hg) was lower than the hypertension control rate based on ABPM (24 hours < 130/80 mm Hg), which suggests the presence of a white coat effect detected in ABPM. The increasing number of antihypertensive drugs prescribed was associated with indicators of greater severity of the hypertensive situation, translated by higher values of age (54+16 to 63+13 years), BMI (27.3+4.0 to 29.7+4.8 Kg/m2), casual BP (148/89+20/13 to 160/88+25/16 mmHg), 24-hour BP (128/75+13/9 to 137/75+18/12 mmHg), and aortic stiffness index (0.37+0.18 to 0.46+0.19), and a lower decrease in nocturnal systolic BP (11.9+7.7 for 8.4+9.2 %) all p<0.01, as well as to more frequent use of diuretics, angiotensin receptor antagonists, beta-blockers and calcium antagonists. The study confirms the advantage of ABPM in the stratification of cardiovascular risk, in the evaluation of real blood pressure control and in the diagnosis of the white coat phenomenon in medicated hypertensive patients.